1997
DOI: 10.1155/np.1997.41
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences of Serotonin‐Mediated Synaptic Plasticity in the Chicken Spinal Cord With Development and Aging

Abstract: Previous studies in our laboratory /3,17/ have demonstrated that serotonin (5-HT) appears to have a trophic-like effect in enhancing synapse formation and maintenance in both the developing and the adult central nervous system. In the present study, we focused on age-related changes in the density of the axosomatic and axodendritic synapses and the number of 5-HT-positive fibers in the chicken spinal cord, with special reference to differences between the ventral (laminae VII and IX) and the dorsal (lamina I) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…It would appear therefore that dendritic change is a common feature affecting most central neurons such as pyramidal neurons in the medial prefrontal cortex (Grill and Riddle, 2002), motor cortices (Nakamura et al, 1985) and hippocampus (Luine et al, 2011), cerebellar Purkinje neurons (Zhang et al, 2010) and retinal ganglion cells (Samuel et al, 2011). It is suggested that regression in dendritic arbor and loss of dendritic spines on layer III, layer V primary somatosensory cortical neurons or hippocampal CA1 pyramidal neurons as observed in this study in aging rats may reflect different degrees of degenerative changes that might be induced by regional changes in trophic support (Chen et al, 1997) or in neuronal activity (Grill and Riddle, 2002). In the clinic, such dendritic arbor regression and reduction in dendritic spine density of cortical pyramidal neurons may contribute to behavioral dysfunctions as observed in aging including cognitive loss, anxiety, fatigue, poor concentration and memory, and confusion.…”
Section: Discussionmentioning
confidence: 52%
“…It would appear therefore that dendritic change is a common feature affecting most central neurons such as pyramidal neurons in the medial prefrontal cortex (Grill and Riddle, 2002), motor cortices (Nakamura et al, 1985) and hippocampus (Luine et al, 2011), cerebellar Purkinje neurons (Zhang et al, 2010) and retinal ganglion cells (Samuel et al, 2011). It is suggested that regression in dendritic arbor and loss of dendritic spines on layer III, layer V primary somatosensory cortical neurons or hippocampal CA1 pyramidal neurons as observed in this study in aging rats may reflect different degrees of degenerative changes that might be induced by regional changes in trophic support (Chen et al, 1997) or in neuronal activity (Grill and Riddle, 2002). In the clinic, such dendritic arbor regression and reduction in dendritic spine density of cortical pyramidal neurons may contribute to behavioral dysfunctions as observed in aging including cognitive loss, anxiety, fatigue, poor concentration and memory, and confusion.…”
Section: Discussionmentioning
confidence: 52%
“…In both the rat (monoaminergic innervation − 3 versus 24 months; Ranson et al, 2003) and chicken (serotonin-mediated innervation – up to 2 years; Chen et al, 1997), innervation decreases with age in the ventral horn, yet it is retained or even increases during ageing in other areas, such as for 5-HT positive fibers in the dorsal horn of the chicken. Comparison of axosomatic and axodendritic synaptic density from hatching to 2 years in lamina I of the dorsal horn and lamina IX of the ventral horn shows opposite changes in synaptic density, with an increase in I and a decrease in IX (e.g., for the latter, axodendritic density changes from ~24 to ~13 synapses per 200 square micrometers).…”
Section: Brainstem Cerebellum and Spinal Cordmentioning
confidence: 99%
“…Coronal serial sections were cut at a thickness of 40 m on a freezing microtome, and every third section was used for 5-HT immunohistochemistry staining. The free-floating sections were pretreated overnight with 0.3% triton X-100/0.01 M PBS, then were blocked by 5% normal goat serum (NGS, Invitrogen, Carlsbad, CA, USA), prior to an incubation with anti-5-HT antiserum (at 1:10,000 dilution for 4 h at 37 • C,) (Chen et al, 1997). Biotinated anti-rabbit antibody (Vector Laboratories, Burlingame, CA, USA) was used as the secondary antibody, at 1:400 dilution for 1 h, followed by a Vecstastain ABC kit (Vector Laboratories).…”
Section: Tissue 5-ht Immunohistochemistrymentioning
confidence: 99%